2018
DOI: 10.1108/jeas-04-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Performance indicators for public private partnership (PPP) projects in Malaysia

Abstract: Purpose The purpose of this paper is twofold: first, to identify the important performance indicators used in assessing public private partnership (PPP) performance in terms of the two aspects of PPP which are “financing and markets” and “innovation and learnings”; and second, to investigate the differences in the perception between public and private sectors on the importance of performance indicators in terms of the two aspects of PPP. Design/methodology/approach Using a questionnaire survey, 237 completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…The use of KPIs in PPP project performance has been used in various studies. These KPIs have revolved around physical characteristics of projects, financing and marketing indicators, innovation and learning indicators, stakeholder indicators and process indicators (Mohamad et al, 2018;Hashim et al, 2017;Yuan et al, 2012). Yuan et al (2012) revealed that stakeholders perceive success and performance of PPPs as a commitment between public and private sector, appropriate risk-sharing, allocation and transfer, constructability and maintainability of project, project technical feasibility and effective knowledge transfer.…”
Section: Jopp 212mentioning
confidence: 99%
“…The use of KPIs in PPP project performance has been used in various studies. These KPIs have revolved around physical characteristics of projects, financing and marketing indicators, innovation and learning indicators, stakeholder indicators and process indicators (Mohamad et al, 2018;Hashim et al, 2017;Yuan et al, 2012). Yuan et al (2012) revealed that stakeholders perceive success and performance of PPPs as a commitment between public and private sector, appropriate risk-sharing, allocation and transfer, constructability and maintainability of project, project technical feasibility and effective knowledge transfer.…”
Section: Jopp 212mentioning
confidence: 99%
“…In PPPs, training is considered an important performance indicator that affects the process of the PPP. Employees should receive training to gain new knowledge and improve individual and organizational performance [52,53]. Therefore, we propose the fifth hypothesis:…”
Section: Perceived Public Attitudementioning
confidence: 99%
“…Political risk: mainly includes political decision-making and political opposition. During the project approval stage [30], the government does not understand the relevant policies of the corridor project, and lacks relevant engineering practice management experience [31,32], which may lead to the approval of some pipe gallery projects that are not suitable for PPP mode; in some areas due to the public's comprehensive project of the corridors Insufficient recognition may cause public dissatisfaction and opposition in the early stage of project construction.…”
Section: Utility Tunnel Application Ppp Mode Risk Divisionmentioning
confidence: 99%